Oglachty, Russland. Die Menschen von Oglachty in Südsibirien: Welchen Platz hatten sie in der Geschichte Eurasiens im frühen ersten Jahrtausend n. Chr.? Die Arbeiten des Jahres 2019 (Projekte »Silk Road Fashion« und »BAYCHRON«) - Pankova, Sveltana V.; Long, Tengwen; Leipe, Christian; Tarasov, Pavel E.; Wagner, Mayke (e-Forschungsberichte des DAI, 2020)
The people of Oglakhty in South Siberia: What place did they have in the history of Eurasia in the early first millennium AD? When a shepherd fell into an old grave pit on the bank of the Yenisei River in 1902 and Alexander Adrianov uncovered another sixteen graves in the following year, research began in Oglakhty that still offers as many challenges as it did a hundred years ago. This is due to the unusual treatment of the deceased that was not previously practiced in this region, the grave goods and their age. Our project aims toimprove the accuracy of the determined age of grave no. 4 in Oglakhty, in order to understand the emergence of new cultural phenomena in southern Siberia and ultimately to be able to connect it with the overall mechanism of the formation processes in East Asia during the early first millennium AD. In this first work report we present the main features of the finding and outline the open research questions.